Emotion dysregulation across the span of eating disorder symptoms: Findings from a community sample of adolescents. Issue 11 (24th September 2021) - Trompeter, Nora; Bussey, Kay; Forbes, Miriam K.; Mond, Jonathan; Hay, Phillipa; Cunningham, Mitchell L.; Mitchison, Deborah
Abstract: Objective: Emotion dysregulation is proposed as a key factor within eating disorder pathology. However, less is known about specific emotion regulation difficulties experienced by adolescents with varying levels of eating disorders symptoms. The present study examined the relationship between eating disorder behaviors and specific facets of emotion dysregulation, and differences in emotion dysregulation between eating disorder diagnostic groups. Method: Participants were 2, 783 adolescents, 11–19 years ( M  = 14 years, 9 months, SD = 1 year, 6 months), who completed self‐report measures as part of the EveryBODY study. Adolescents were identified as not having eating disorder symptoms ( n  = 2, 122) or meeting diagnostic criteria for symptoms of specific eating disorder, including: anorexia nervosa or atypical anorexia nervosa ( n  = 57), bulimia nervosa ( n  = 136), binge‐eating disorder ( n  = 57), other specified feeding or eating disorder characterized by binge eating or purging ( n  = 381), and unspecified feeding or eating disorder ( n  = 30). Results: Binge eating, driven exercise, and fasting were each uniquely associated with emotion dysregulation, whereas purging was not. Similar findings were obtained within specific domains of emotion dysregulation. Findings from diagnostic groups showed a significant main effect of diagnosis on overall emotion dysregulation and most domains of emotion dysregulation. Adolescents with eating disorder symptoms consistently reported higher emotion dysregulation compared to those without these symptoms. Discussion: Findings indicate that emotion dysregulation is a key factor across eating disorder pathology, and potential treatment target across the spectrum of eating disorder diagnoses in adolescents.